VALIDITY OF STUDENT WORKSHEET DEVELOPMENT BASE ON PBM WITH A SCIENTIFIC APPROACH IN THE MATERIAL SPECIAL LINES AND CIRCLES ON TRIANGLES - Finola Marta Putri (Jurnal Prinsip Pendidikan Matematika, 2021)
This research is in development research, aiming to develop student worksheets material Special Lines and Circles in Triangles based on Problem Based Learning with a scientific approach. This Student Work Sheet can be used as a learning resource by students in the Mathematics subject at School I in the Mathematics Education Department, Faculty of Tarbiyah and Teacher Training (FITK) UIN Syarif Hidayatullah Jakarta (UIN Jakarta). This study uses a 4-D development model consisting of four steps: defining, designing, developing, and disseminating. This research is limited to the development stage. The data collected is in the form of data on the validity of the Student Work Sheet. Validity data collected by circulating a validation questionnaire to two validators. The validity data is processed quantitative and qualitative. The data obtained based on the results of the analysis are(1) the quality of the material, (2) aspects of language and (3) overall elements of the presentation of the Student Keja Sheet material developed very valid criteria. Conclusion of The Student Work Sheet material Unique Lines and Circles on Triangles based on Problem-Based Learning with a scientific approach developed is suitable for use as a learning resource for students in the School Mathematics course I.